Influence of glycemic index and glycemic load of the diet on the risk of overweight and adiposity in childhood - Kellen Cristine Silva; Luciana Neri Nobre; Sofia Emanuelle de Castro Ferreira Vicente; Lidiane Lopes Moreira; Angelina do Carmo Lessa; Joel Alves Lamounier
Abstract Objective: To investigate the association between the glycemic index and the glycemic load of the diet with the risk of overweight and high adiposity in children with 5 years of age. Methods: Cross-sectional study nested in a cohort of 232 children born and living in Diamantina (MG, Brazil). Parents and/or guardians provided the food intake data, using a semiquantitative food frequency questionnaire, past history and socioeconomic conditions. Anthropometric and fatness data were collected from the children. The dietary glycemic index and the glycemic load were calculated from the food intake. The glycemic index and glycemic load effect on overweight and adiposity in children was assessed by the Poisson regression (p<0.05). Results: The prevalence of overweight by body mass index was 17.3%, and high adiposity was observed in 3.4% and 6.9% by triceps skinfold and subscapular skinfold, respectively. No difference was reported between the mean body mass index, triceps skinfold and subscapular skinfold according to the glycemic index and glycemic load tertiles; however, the overweight group presented a higher carbohydrate intake (p=0.04). No association was found between glycemic index and glycemic load with overweight and adiposity among the children assessed. Conclusions: The glycemic index and glycemic load of the diet were not identified as risk factors for overweight and adiposity in this cross-sectional study.